KEPADATAN DAN KERAGAMAN FUNGI MIKORIZA ARBUSKULA PADA PERTANAMAN JAGUNG (Zea mays L.) - Abdul Rasyid; Iskandar M. Lapanjang; Henry N. Barus (Universitas Tadulako, 2016)
Utilization of arbuscular mycorrhizal fungi (AMF) is aimed at increasing crop productivityon marginal soils.AMF role as natural microorganisms areenhancing the absorption of nutrient, especially P,helping the plant to be able to withstand drought conditions as their hyphae are able to penetrate soil pores thus expanding the areas of water absorption, and protecting plant roots against pathogen attacks. Intensive planting would disturb the populationand development of the AMF. The purpose of this study was to observe the status of AMF sporeson maize (Zea mays L.).This study used a randomized block design (RAK) with 6 treatments and 5 replicates so that there were 30 experimental units.Factors studiedare several types of AMF based on the color of the corn plant area.Data fromthe study concluded that observationof AMFspores horizontally (H1, H2, and H3) showed no difference in the density of spores. In contrast, the treatment of vertical AMF(V1, V2, and V3) decreases the number of spores with increasing soil depth. The diversity ofcolorbased AMF spores morphological types showed that there are four groups of colors i.e.yellow, brown , black, and translucent.In the Horizontal position, most AMF spores from left to right are black, while in the vertical position the dominant color is yellow. The natural spore density in the rhizosphere of maize(Zea mays L.)generally ranges from 35 – 124 spores/10 g soil. Keywords : Arbuscularmycorrhizal fungi (AMF ), and maize.